HUBUNGAN AKTIVITAS FISIK DAN POLA MAKAN TERHADAP KADAR LDL PADA MAHASISWA - Tasrif Ahmad (Journal of Nursing and Health, 2024)
Low Density Lipoprotein (LDL) is an atherogenic lipoprotein particle. Because, it is one of the triggers for the formation of atherosclerotic plaques. LDL is a lipoprotein that functions to carry cholesterol to peripheral tissues and break down membranes and steroid hormones. LDL levels exceeding normal will cause the accumulation of atherosclerotic plaques resulting in hyperlipidemia conditions. Until now, hyperlipidemia control is eating pattern, physical activity, and the use of drug therapy. The results of a survey of physical activity and eating pattern conducted by researchers showed that the majority of students had low levels of physical activity and an unhealthy eating pattern. This study aims to determine the relationship of physical activity and Eating Pattern to LDL levels in Bachelor of Applied Medical Laboratory Technology students at the National College of Health Sciences. This study used purposive sampling technique with a total of 30 respondents with an age range of 18-25 years. Physical activity was measured for one week using a logbook along with the IPAQ questionnaire and Eating Pattern measured by the OREB questionnaire. The data were analyzed using multiple linear regression test with SPSS. The results of the Shapiro-Wilk normality test were obtained with a sig>0.05 value and multiple linear regression test with a sig>0.05 value. In accordance with the basis for decision making in the F test, it can be concluded that the hypothesis is not accepted or in other words, Physical Activity and Eating Pattern are not related to LDL levels.